A prospective randomized controlled trial to study the effect of preoperative and intraoperative magnesium over postoperative ileus and postoperative pain in major non–laparoscopic abdominal surgeries - Bathina, A. R. Vishal Varma; Peetani, Rama Krishna; Vaitla, Viswa Teja (International Surgery Journal, 2019)
Background: The objective of the study were postoperative pain on 1st postoperative hour and 2, 4, 12, 24th postoperative hour as per numeric rating scale (NRS); total dose of postoperative analgesic consumption; postoperatively time of first appearance of bowed sounds; postoperatively time of first passage of flatus. Methods: A randomized controlled study will be performed. Patients of ASA 1 and 2, scheduled for major abdominal (GI) surgery, were divided into magnesium group and control group. Serum magnesium levels are estimated in both groups. Magnesium group receives 40 mg/kg of magnesium sulfate in 100 cc NS 30 minutes before the induction* as Intravenous drip, followed by 10 mg/kg/hr during the intraoperative hours. Control group receives the same volume of isotonic saline solution. Intra-operative hemodynamic parameters are evaluated constantly by recording pulse rate, blood pressure and Spo2. Further, post- operative analgesic will be ensured by epidural top-up using bupivacaine and tramadol when patients complaints of pain or when monitored with numeric rating scale (NRS). Postoperative patient pain is going to be evaluated in post-anesthetic care unit (PACU)/ SICU by numeral rating scale (NRS) during 1st hour, 2nd hour, 4th hour, 12th hour and 1 day, total dose of post-operative analgesic consumption will be recorded. Results: Of the 60 patients studied, 30 belong to magnesium group for which pre-operative and intraoperative intravenous magnesium (cases). Remaining 30 were given equal amounts of preoperative and intraoperative normal saline given (controls). Conclusions: The results of present study suggests that pre and intra operative. Magnesium as an adjunct to epidural analgesia reduces postoperative pain pre-operative and intra operative IV mg reduces post-operative ileus duration.